Optimisation of the conditions for stripping voltammetric analysis at liquid-liquid interfaces supported at micropore arrays: a computational simulation - Strutwolf, J.; Arrigan, Damien (Springer, 2010)
Micropore membranes have been used to form arrays of micro interfaces between immiscible electroly tesolutions (μITIES) as a basis for the sensing of non-redoxactiveions. Implementation of stripping voltammetry as asensing method at these arrays of μITIES was applied recently to detect drugs and biomolecules at low concentrations. The present study uses computational simulation to investigate the optimum conditions for stripping voltammetricsensing at the μITIES array. In this scenario, thediffusion of ions in both the aqueous and the organic phasescontributes to the sensing response. The influence of the preconcentration time, the micropore aspect ratio, the location of the micro interface within the pore, the ratio of the diffusion coefficients of the analyte ion in the organic and aqueous phases, and the pore wall angle were investigated. The simulations reveal that the accessibility of the microinterfaces during the preconcentration period should not be hampered by a recessed interface and that diffusional transport in the phase where the analyte ions are preconcentrated should be minimized. This will ensure that the ions are accumulated within the micropores close to the interface and thus be readily available for back transferduring the stripping process. On the basis of the results, an optimal combination of the examined parameters is proposed,which together improve the stripping voltammetric signal and provide an improvement in the detection limit.